CHANGES IN OXIDATION AND REDUCTION POTENTIAL (Eh) AND pH OF TROPICAL FISH DURING STORAGE - Eko Susanto; Tri Winarni Agustini; Eko Prasetyo Ritanto; Eko Nurcahya Dewi; Fronthea Swastawati (JOURNAL OF COASTAL DEVELOPMENT, 2011)
Four tropical fish species, Thunnus albacares (Yellowfin tuna), Ephinephelus striatus (Nassau Grouper), Cyprinus carpio (Carp), and Osphronemus gourami (Gouramy), were assayed for oxidation reduction potental (Eh) and pH in different temperature,i.e.  ambient and chilled temperature.  Every species has different pattern of Eh and pH values. Eh values of tropical freshwater fish were higher than tropical marine fish, however pH values  four tropical fish have same trend. The rates of the Eh and pH changing in four tropical fish were faster at ambient storage and they were slower at chilled storage. The present study also demonstrated the relationship between Eh and pH.